A Comprehensive Review of Nuclear-Renewable Hybrid Energy Systems: Status, Operation, Configuration, Benefit, and Feasibility - Arefin, Md Arman; Islam, Mohammad Towhidul; Rashid, Fazlur; Mostakim, Khodadad; Masuk, Nahid Imtiaz; Islam, Md. Hasan Ibna (Frontiers in Sustainable Cities, 2021)
One of the biggest concerns of the present century is energy security and climate change. Further, studies suggest that there would be a huge lack of fossil fuels in near future. Moreover, in terms of cleaner production, the most popular and practiced way of power generation is renewable energy sources which are intermittent in nature, require large land area, and also dependent on geographic positions and climatic conditions. Besides, nuclear energy is also having some limitations including government policies and public apprehensions. To overcome these hurdles, these two carbon-free technologies can be integrated and form a nuclear-renewable hybrid energy system (N-R-HES). Literature related to the proposed systems is extremely rare and the systems are not yet well-developed. Keeping that into concern, this paper discusses the operation, status, prospects, and benefits of N-R-HES. Various possible integration techniques along with their operation are discussed in detail. Moreover, six aspects of interconnections are identified: electrical, thermal, chemical, mechanical, hydrogen, and information. The paper also discusses the reactor licensing, permitting procedures along the different benefits of N-R-HES. Additionally, research limitations and needs are identified for further exploration of the topic throughout the paper.